Virtual center for the paradigmatic studies - Tadeusz Krupa (Foundations of Management, 2020)
The Virtual Center for Paradigmatic Studies is a serious profession and, at the same time, a beneficial offer addressed to people who treat the process of their education and professional development both at home and in the academic environment as a unique life opportunity. This article presents material constituting the program and the basis for conducting theoretical and practical work at the Virtual Center for Paradigmatic Studies. The published material covers such issues as: the description of the Gorbatov's characterization principle, the theoretical correctness of the model of functioning, an example of the Semantic Model of 5 Projects, effective search for forbidden graph figures, the essence of functions that integrate semantic graphs, multi-object semantic sequences of events, the structure and purpose of Hasse diagrams.
Keywords: C58; E27; G11; G17; O22; 650; Gorbatov's characterization principle; model of functioning Ψa; model of structure Ψb; Hasse diagram; forbidden graph figures (FGF); sentence variable (SV); sequences of sentence variables (SSV)